La iglesia altomedieval de la Silla del Papa (Tarifa, Cádiz) - Sonia Gutiérrez Lloret; Bastien Lefebvre; Pierre Moret (Mélanges de la Casa de Velázquez, 2017)
The investigations carried on since 2014 in the old oppidum of Silla del Papa have revealed the existence of a high mediaeval church associated with a tall edifice that is yet little known. This modest-sized church has a rectangular nave measuring 10 x 6.50 m merging into a quadrangular apse of 3.50 x 4.90 m on the east side, with adjoining enclosures on the north and south sides, including a secondary apse. Both apses once contained an altar set on a cylindrical pillar with a loculus for relics. Sounding has revealed the presence of several tombs inside the nave. The church may have been founded as a euergetic work by Pymenius, Bishop of Asidonia, in the 7th century. The building continued to be occupied, for domestic use, after the Arab-Berber conquest, until it was finally abandoned in the time of the Emirates.